Nutrition-related knowledge and body mass índex in a sample of portuguese university students - Vasconcelos, Carlos (2020)
INTRODUCTION: Being overweight or obese is associated with several health problems. In Portugal, 59.1% of the adult population (> 20 years old) are overweight and 24.0% obese. Nutrition-related knowledge is one important factor that influence healthy eating patterns. OBJECTIVES: The purpose of this study was to analyze the association between nutrition-related knowledge and body mass index in a sample of Portuguese university students. METHODOLOGY: This was a cross-sectional study performed in 75 Portuguese university students (40 female; 22.1 ± 3.8 years of age). Nutrition-related knowledge was assessed using the Portuguese reduced version of the Nutritional Knowledge Questionnaire. This version of the questionnaire consists of three sections (dietary recommendations [0-6 points]; sources of nutrients [0-34 points]; diet-disease relationship [0-16 points]), totaling a maximum score of 56 points. Body mass index was calculated through self-reported body weight (kg) and body height (m) data with the formula body weight (kg) / body height (m)2. RESULTS: Total score of the Portuguese reduced version of the Nutritional Knowledge Questionnaire was 31.5 ± 8.8 points. The mean value of body mass index was 22.9 ± 2.9 kg/m2. Through the use of Pearson correlation, we determine that the association between nutrition-related knowledge and body mass index is positive and non-significant (r = 0.119; p = 0.309). CONCLUSIONS: Our study revealed that there was no significant association between levels of nutrition-related knowledge and body mass index in this sample of Portuguese university students.